Outbreak of Gastrointestinal Infections Caused by Yersinia enterocolitica in Children, Medellín, Colombia - Galvis, Julián C.; Beltrán, Claudia; Sierra, Elizabeth; Montaño, Aleyda M.; Ramírez, Faiver; Villa, Pablo; Diaz, Alejandro; Robledo, Carlos; Robledo, Jaime (Journal of Pediatric Infectious Diseases, 2023)
Objective In this study, we describe the clinical and epidemiological characteristics of a cluster of children with acute gastrointestinal (GI) infection caused by Yersinia enterocolitica in Medellín, Colombia.Methods A retrospective descriptive observational study was performed with the information recorded in clinical charts of GI infection cases caused by Y. enterocolitica in pediatric population of two hospital institutions in Medellín, Colombia. The microorganism identification was performed directly from stool samples using molecular biology techniques and from stool cultures using mass spectrometry. Space-time simulations and antibiotic susceptibility profiles were performed using Whonet 5.6 and Clinical and Laboratory Standards Institute 2020 guide.Results A total of 37 cases were identified in children younger than 15 years; between November 2020 and January 2021, 45.9% of cases were in children aged 1 to 5 years. Most children had diarrhea (97.3%) and fever (67.6%), 21.6% had abdominal pain and vomiting, and 13.5% had hyporexia. Sixteen of the patients (43.2%) received azithromycin, 24.3% (n = 9) received ceftriaxone, and 13.5% (n = 5) received a combined treatment of ceftriaxone and azithromycin or azithromycin and metronidazole. Based on space-time simulations, the clonality analysis and the characteristics of the cases suggest a community outbreak of unknown origin.Conclusion Our findings confirm the occurrence of an outbreak related to Y. enterocolitica from the community whose source could not be identified. Although it is presumed that the frequency of this microorganism is low in these regions, the use of new diagnostic tools in clinical microbiology allowed the early identification of the epidemiological event.
Keywords: yersiniosis; MALDI-TOF MS; space-time simulations; clusters; clonality